(untitled) - Loucks, William N. (New York, 1938)
This text focuses on comparisons between the three major types of economic systems in the world today - capitalism, transition economies of the former Soviet Union, and the economies of the LDC's and developing countries.
Keywords: Comparative economics,Kinh tế so sánh